BOMCAR 7: Developing Board Game Card Media for Enhanced Grammar Learning Among Indonesian EFL Students - Aliyyah, Naily Samakhatal; Shofiyuddin, Muh. (Universitas Pendidikan Mandalika, 2025)
This study aims to develop and evaluate BOMCAR 7 (Board Game Card Media Tenses Adventure), a game-based learning tool designed to enhance grammar proficiency through interactive instruction. Using a one-group pretest-posttest design, the research investigates the effectiveness of board game card media among 30 tenth-grade students at a private Islamic senior high school in Jepara, Indonesia. The development followed the ADDIE model, incorporating needs analysis, expert validation, and field testing. The board game focused on simple present tense structures within the